PENGARUH WORK FROM HOME (WFH) TERHADAP EFEKTIVITAS KERJA DAN PRODUKTIVITAS PEGAWAI BALAI BESAR PENGAWAS OBAT DAN MAKANAN (BBPOM) PEKANBARU - Ramadhani Tio Muhammad; Roesdi Rosnelly; Fitri Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Work from Home (WFH) on Work Effectiveness and Employee Productivity Center for Food and Drug Administration (BBPOM) Pekanbaru. The population of study included all employee as civil servant at BBPOM Pekanbaru, totaling 90 people and sampling technique used was saturation sampling. Primary was collected by questionnaire as an instrument to prove the result of research. Structural Equation Model (SEM) with SmartPLS version 3 was used as methods of data analysis. The results were: 1) Work from Home (WFH) had a positive and significant effect on Work Effectiveness employee Center for Food and Drug Administration (BBPOM) Pekanbaru; 2) Work from Home (WFH) had a positive and significant effect on Work Productivity employee Center for Food and Drug Administration (BBPOM) Pekanbaru; 3) Work Effectiveness had a positive and significant effect on Work Productivity employee Center for Food and Drug Administration (BBPOM) Pekanbaru; 4) Work from Home (WFH) had a positive and significant effect on Work Productivity throughwork Work Effectiveness employee Center for Food and Drug Administration (BBPOM) Pekanbaru.Keyword: Work from Home (WFH), Work Effectiveness, Work Productivity